2010
DOI: 10.1080/08964289.2010.525263
|View full text |Cite
|
Sign up to set email alerts
|

Use and Evaluation of a CD-ROM-Based Decision Aid for Prostate Cancer Treatment Decisions

Abstract: The survival advantages associated with different treatments for localized prostate cancer (PCa) continue to be uncertain. We evaluated patients' use of an interactive CD-ROM-based decision aid designed to improve informed decision making about PCa treatment. Newly diagnosed, early-stage PCa patients who had not made a treatment decision completed a baseline telephone interview (N = 132), were mailed the CD-ROM, and completed a one-month follow-up interview (N = 120; 91%). Compared to non-users (21%), CD-users… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(52 citation statements)
references
References 28 publications
1
51
0
Order By: Relevance
“…We excluded one trial in which a substantial proportion of patients did not have localized prostate cancer (34% had “intracapsular” prostate cancer, 46% had “locally advanced” prostate cancer, and 20% had “distant” prostate cancer) . Three studies (21%) confirmed the accuracy of our consensus data extraction, 8 studies (57%) corrected some errors and/or added additional information, and 3 groups (21%) did not respond to our requests . Ten RCTs were conducted in North America, and the remaining studies were conducted in Europe (The Netherlands, Spain, United Kingdom) and Australia (Table ) .…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…We excluded one trial in which a substantial proportion of patients did not have localized prostate cancer (34% had “intracapsular” prostate cancer, 46% had “locally advanced” prostate cancer, and 20% had “distant” prostate cancer) . Three studies (21%) confirmed the accuracy of our consensus data extraction, 8 studies (57%) corrected some errors and/or added additional information, and 3 groups (21%) did not respond to our requests . Ten RCTs were conducted in North America, and the remaining studies were conducted in Europe (The Netherlands, Spain, United Kingdom) and Australia (Table ) .…”
Section: Resultsmentioning
confidence: 95%
“…Screening titles, abstracts, and full texts yielded 14 eligible RCTs (Fig. ) . We excluded one trial in which a substantial proportion of patients did not have localized prostate cancer (34% had “intracapsular” prostate cancer, 46% had “locally advanced” prostate cancer, and 20% had “distant” prostate cancer) .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A growing number of decision aids are being provided online as adults are using the Internet in greater numbers to access health information [13,14]. Additionally, studies of men with PCa found that the Internet and electronically based information were important sources of information regarding both screening and diagnosis [15][16][17][18]. In general, online health information seekers say they feel more confident in starting a discussion with their doctor than those who do not use the Internet to find health information [19].…”
Section: Introductionmentioning
confidence: 99%
“…To help patients with localized prostate cancer make an informed treatment decision, intervention strategies in current decision aids include communication skills training or role modeling to improve communication between patients, their family members, and providers for clinical encounters [1416]; providing information using multimedia [14,15,1724]; facilitating value clarification and reducing decision conflicts [14,18,19,22,24]; and providing consultation plans and preparation materials [19,2325]. Although improving communication skills for patients and their family members is one of the integral strategies in decision aid interventions for localized prostate cancer treatment choices, a recent systematic review and meta -analysis [5] found that patient-provider communication was evaluated only in one clinical trial using a Likert-type scale after consultation visits [16].…”
Section: Introductionmentioning
confidence: 99%